ANALISIS PENGARUH KEPEMIMPINAN, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN BAGIAN PRODUKSI PADA PT. UNITED ROPE MEDAN - Simbolon, Sahat; Simbolon, Dwi Maria; Parhusip, Poltak T. (UNIKA Santo Thomas, 2022)
This study aims to describe the influence of leadership, communication and work environment on job satisfaction of employees in the production department at PT. United Rope Medan. The research subject was conducted on employees of the production division of PT. United Rope Medan with a population of 577 people. The research have 236 sample using simple random sampling method.The instrument used is a questionnaire to collect data from the variables of leadership, communication and work environment and employee job satisfaction. The data analysis technique used is validity test, reliability test, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, T test, F test and coefficient of determination test. The results of the analysis in the variables of leadership, communication and work environment in the very good category, while the variable job satisfaction in the very good category. The results of the analysis for the variables of leadership, communication, work environment and employee job satisfaction are in the very good category at PT. United Rope Medan. Based on the partial analysis, leadership have a positive and significant influence on job satisfaction, communication have a positive and significant influence on job satisfaction and work environment have a positive and significant influence on job satisfaction. Based on the simultan analysis, leadership, communication and work environment have a positive and significant influence on job satisfaction of production employees at PT. United Rope Medan. The contribution of leadership, communication and work environment to increase job satisfaction variable is 0.821 or 82.1%, while the remaining 0.179 or 17.9% is influenced by other variables not examined in this study such as career path, work conflict, work motivation and others. etc.